Individual differences in learning and biogenic amine levels influence the behavioural division between foraging honeybee scouts and recruits. Issue 2 (2nd November 2018) - Cook, Chelsea N.; Mosqueiro, Thiago; Brent, Colin S.; Ozturk, Cahit; Gadau, Jürgen; Pinter‐Wollman, Noa; Smith, Brian H.
Abstract: Animals must effectively balance the time they spend exploring the environment for new resources and exploiting them. One way that social animals accomplish this balance is by allocating these two tasks to different individuals. In honeybees, foraging is divided between scouts, which tend to explore the landscape for novel resources, and recruits, which tend to exploit these resources. Exploring the variation in cognitive and physiological mechanisms of foraging behaviour will provide a deeper understanding of how the division of labour is regulated in social insect societies. Here, we uncover how honeybee foraging behaviour may be shaped by predispositions in performance of latent inhibition (LI), which is a form of non‐associative learning by which individuals learn to ignore familiar information. We compared LI between scouts and recruits, hypothesizing that differences in learning would correlate with differences in foraging behaviour. Scouts seek out and encounter many new odours while locating novel resources, while recruits continuously forage from the same resource, even as its quality degrades. We found that scouts show stronger LI than recruits, possibly reflecting their need to discriminate forage quality. We also found that scouts have significantly elevated tyramine compared to recruits. Furthermore, after associative odour training, recruits have significantly diminished octopamine in their brains compared to scouts. These results suggest that individual variation in learning behaviour shapes the phenotypic behavioural differences between different types of honeybee foragers. These differences in turn have important consequences for how honeybee colonies interact with their environment. Uncovering the proximate mechanisms that influence individual variation in foraging behaviour is crucial for understanding the ecological context in which societies evolve. Abstract : Honeybees have mastered the exploration–exploitation trade‐off by dividing foraging labour. Here, the authors report that underlying this division of labour is variation in learning ability: scouts ignore familiar odours while recruits readily learn novel and familiar odours. Further, scouts and recruits have different quantities of biogenic amines in their brains, influencing their behaviour.